Designing Anti‐Icing Surfaces by Controlling Ice Formation. Issue 17 (17th August 2021) - Zhou, Xiaoteng; Sun, Yuling; Liu, Jie
Abstract: Understanding the formation of ice from supercooled water on a surface is a matter of fundamental importance and general use. Kinetics of ice nucleation and ice growth on solid surfaces are actively studied, based on which effective anti‐icing surfaces are designed. This review introduces one major breakthrough of experimental estimation of the critical ice nucleus size in heterogenous ice nucleation (HIN). Besides that, targeted anti‐icing strategies are summarized according to the icing steps: suppression of ice nucleation, regulation of ice growth, and reducing ice adhesion. Factors such as crystal lattice match, charge, and ions, etc., are found to have determined effects on the HIN in specific circumstances. This promotes the study of surfaces with ice nucleation inhibition properties. Recent research about distinct ice growth patterns on hydrophobic and hydrophilic surfaces provides a new insight of designing icephobic surfaces by regulating ice growth or spreading processes. At last, effective surfaces including lubricated surface, low interfacial toughness surface, and superhydrophobic surface are developed to significantly reduce ice adhesion strength. The robustness, cost, and manufacture complexity can be problems that need to be considered for the widespread practice of anti‐icing surfaces. Abstract : The bio‐inspired anti‐icing strategies are summarized according to the ice formation steps: suppression of ice nucleation, regulation of ice growth, and reducing ice adhesion. The aim of this review is to help researchers better understand the ice formation processes and the mechanism of anti‐icing strategies and to give some advice on the development of anti‐icing surfaces.